AB0274 USE OF TNF-INHIBITORS BIOSIMILARS IN CHRONIC INFLAMMATORY ARTHRITIDES: A THREE-YEAR EXPERIENCE IN A LARGE MONOCENTRIC COHORT OF PATIENTS FROM THE NORTH-EAST ITALY. (2nd June 2020) - Astorri, D.; Ometto, F.; Friso, L.; Raffeiner, B.; Botsios, C.; Doria, A.
Abstract : Background: In recent years several biosimilars (BS) of tumour necrosis factor inhibitors (TNF-i) were introduced. At the Padova University Hospital the first BS of etanercept (bsETN) was available in October 2016 and the BS of adalimumab (bsADA) was available in November 2018. Objectives: The objectives of the study were to evaluate the rate of bioriginator-biosimilar (BO-BS) switch in all patients with rheumatoid arthritis (RA), psoriatic arthritis (PSA) and axial spondiloarthritis (axSpA) in the cohort of the Padova University Hospital and to examine factors favouring BO-BS switch. Secondly, we investigated survival of BO-BS switch and BO treatment and factors associated with longer treatment survival. Methods: We considered all patients on ETN originator (boETN) treatment when the first bsETN was available (1st October 2016) and all patients on ADA originator (boADA) when bsADA was available (1st November 2018). Patients were followed until 30 August 2019 and were classified as BO-BS switchers if they underwent a switch from either boETN or boADA to BS during the follow-up, otherwise they were considered as continuing BO treatment. Factors associated with BO-BS switch were tested with a multivariable regression analysis. To test the survival of the BO-BS switch and of the BO treatment, Cox regression analysis was used including all variables achiving a p<0.10 in univariate analysis tested with Log-rank test and Kaplan-Meier curves. Results: Among 1208 patients (553 RA, 433 PSA, 215 axSpA), 560 (46.3%) patients switched to bsETN (391) or bsADA (169). Mean disease duration was 16 (14.2) years and mean duration of the bDMARD treatment was 96.3 (56.8) months. After adjustment for potential confounders, factors associated with BO-BS switch were a longer disease duration, a shorter duration of previous bDMARD treatments and diagnosis (Tab.1) RA patients had almost a 3 fold increased likelihood of being switched to BS compared to PSA and axSPA, while difference between PSA and axSPA was not significant. Following Cox regression analysis we observed a longer drug survival in BO-BS switchers compared to those continuing with BO (HR 1.38; 95% C.I. 1.2-1.58; p<0.001) (Fig. 1). A longer drug survival was also associated with a longer disease duration (.15years: HR 1.75; 95% C.I. 1.5-2; p<0.001), longer mean duration of previous bDMARDs (.5years: HR 4.1; 95% C.I. 3.5-4.7; p<0.001), and diagnosis (RA vs PSA: HR 1.22; 95% C.I. 1.02-1.47; p=0.030; RA vs axSpA: HR 0.89 95% C.I. 0.067-0.97; p=0.023; PSA vs axSpA: HR 0.66; 95% C.I. 0.57-0.77; p<0.001) (Fig 2). Conclusion: BO-BS switch was undertaken in almost half of the patients. Patients with longer disease duration and longer bDMARD duration, were the most likely to be switched successfully to BS. BO-BS switching does not affect the survival of the treatment, indeed, it provides sustained effectiveness particularly if undertaken in patients with stable disease activity. Disclosure of Interests: DAVIDE ASTORRI: None declared, Francesca Ometto: None declared, LARA FRISO: None declared, BERND RAFFEINER: None declared, Costantino Botsios: None declared, Andrea Doria Consultant of: GSK, Pfizer, Abbvie, Novartis, Ely Lilly, Speakers bureau: UCB pharma, GSK, Pfizer, Janssen, Abbvie, Novartis, Ely Lilly, BMS